Peningkatan Kompetensi Guru di Tingkat Sekolah Dasar (Current Research in Education: Conference Series Journal, 2022)
At elementary school studies in Indonesia it is need to be adjusted because there were some discrepancies and mistakes, for example the scope of children's ages that made feel them overwhelmed, teachers must struggle to adapt to the current curriculum, and the role of the ministry of education and culture to compile a curriculum. It needs to be reviewed thoroughly to improve the competence of elementary school teachers during the learning process, so they can teach from the curriculum perfectly and properly to students. The research used the data collection method of giving the questionnaire to 7 elementary school teachers. The questionnaire contained 5 questions about the reality felt by the elementary school teachers. After receiving answers from the respondents, the result is the government should be concerned about the teacher’s welfare and there is a teacher training gap. Therefore, elementary school teachers are advised to follow any teacher training that the government has given. This is because in order to make easier for teachers to adapt the any changes of curriculum or learning during in the classroom.